Electronic, magnetic, optical and thermoelectric properties of co-doped Sn1−2xMnxAxO2 (A = Mo, Tc): a first principles insight. Issue 44 (6th October 2022) - Laghzaoui, S.; Lamrani, A. Fakhim; Laamara, R. Ahl; Maskar, E.; Tuxtamishev, Botir Qonishevich; Laref, Amel; Rai, D. P.
Abstract : The electronic, magnetic, optical and thermoelectric properties of Sn1−2 x Mn x A x O2 (A = Mo/Tc) have been examined using density functional theory (DFT) based on the FP-LAPW approach. Abstract : The electronic, magnetic, optical and thermoelectric (TE) properties of Sn1−2 x Mn x A x O2 (A = Mo/Tc) have been examined using density functional theory (DFT) based on the FP-LAPW approach. The results suggested that all the doped compounds show a half-metallic ferromagnet property with a 100% spin polarization at the Fermi level within GGA and mBJ. Moreover, doping SnO2 with double impurities reduces the bandgap. The reduced bandgaps are the result of impurity states which arise due to the Mn and Mo/Tc doping, leading to the shifts of the minima of the conduction band towards the Fermi energy caused by substantial hybridization between transition metals 3d–4d and O-2p states. Also, the (Mn, Mo) co-doped SnO2 system exhibits a ferromagnetic ground state which may be explained by the Zener double exchange mechanism. While the mechanism that controls the ferromagnetism in the (Mn, Tc) co-doped SnO2 system is p–d hybridization. Therefore, the role of this study is to illustrate the fact that half-metallic ferromagnet material is a good absorber of sunlight (visible range) and couples to give a combined effect of spintronics with optronics. Our analysis shows that Sn1−2 x Mn x Mo x O2 and Sn1−2 x Mn x Tc x O2 are more capable of absorbing sunlight in the visible range compared to pristine SnO2 . In addition, we report a significant result for the thermoelectric efficiency ZT of ∼0.114 and ∼0.11 for Sn1−2 x Mn x Mo x O2 and Sn1−2 x Mn x Tc x O2, respectively. Thus, the coupling of these magnetic, optical, and thermoelectric properties in (Mn, A = Mo or Tc) co-doped SnO2 can predict that these materials are suitable for optoelectronic and thermoelectric systems.